(untitled) (Journal of Naval Architecture and Marine Engineering, 2021)
Present analysis elucidates the steady free convective flow of nanofluid over a stretching sheet embedded in a porous medium. Mass transfer analysis with chemical reaction acts a great role in this study. The consideration of viscous dissipation makes the heat transfer analysis more interesting. The governing equations are remodelled as a system of ordinary differential equation adopting similarity transformation and treated numerically by 4th order Runge-Kutta method along with Shooting technique. The present results are compared with the earlier results which gives a good agreement. Some important findings are; porosity acts as aiding force whereas magnetic parameter as resistive force for fluid velocity, larger values of chemical reaction parameter result lower velocity and concentration. The study is relevant in polymer processing, food processing industries and chemical industries.